Self-Disclosure Patterns of Maladjusted Male Adolescents - Paulson, M. J. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to investigate differences in self-disclosure patterns between a group of maladjusted and a group of adjusted male adolescents. A group of 42 male adolescents was selected from a residential treatment centre for behaviorally disturbed adolescents. The mean age was 13.9 years. A second group of 47 male adolescents was selected from the regular school population, with à mean age of 14.1 years. The two groups were differentiated according to degree of behavioral disturbance, as measured by the Behavior Problem Checklist, and according to differences in self-disclosure of various topics to various targets, as measured by the Self-Disclosure Inventory for Adolescents.The research indicated that maladjusted male adolescents disclose significantly less to father and male friend and that they disclose significantly less about the topic of school and more about the topic of peer relations than do adjusted male adolescents. All differences were significant at the .05 level. The conclusion is drawn that maladjusted male adolescents lack significant relationships with a father figure extending to males in general. The importance of these findings is discussed in terms of treatment emphasis with behaviorally disturbed adolescents.